Flow volume measured by duplex ultrasound in native arteriovenous fistula for hemodialysis: a case report - Ronald Winardi Kartika (Journal of Indonesia Vascular Access, 2021)
Background : Native arteriovenous fistula (AVF) is the vascular access of choice for hemodialysis patients. AVF lasts longer than artificial grafts or central venous catheters. In addition, AVF has fewer complications than other vascular accesses. The use of Doppler ultrasound is used to facilitate fistula construction (vascular mapping) including AVF maturation to see if AVF can be used. Doppler ultrasound monitoring for maturation of AV fistulas should be monitored sonographically until the fistula is ready for use, especially when maturation is slow and in patients whose veins cannot easily be assessed by physical examination alone (eg because of obesity). The AVF DUS flow volume measurement may be the only imaging tool that can be used to monitor a fistula even during its maturation. Even so, DUS should always be done before AVF is used for the first time. This examination provides baseline data on vascular access, which can be useful in subsequent tests performed to evaluate functional problems. Case report : A man, 52 years old who has done AV Fitula two weeks ago. Currently patients are using a double lumen catheter (CDL) for routine hemodialysis. One day the patient had his CDL removed. Even though the patient feels thrill in the AV fistula, the nephrorologist still doubts whether the AV fistula is ripe and can be used. For this reason, a Duplex Ultrasound is performed to assess the diameter, velocity flow, PSV and TAMV .By positioning the sample volume in the presumed stenosis site, the Doppler velocity test detects a systolic peak velocity. Conclusion: Color flow Doppler imaging should be used as a tool to screen for areas of high velocity and to aid in the optimal placement of the pulsed Doppler sample volume. The pulsed Doppler sample volume should be set at the smallest size possible to detect discrete changes in blood flow meanwhile doppler ultrasound should be use in monitoring for maturation of AV fistulas